Contributos para o estudo da arquitectura cisterciense, em Portugal, no âmbito do Projecto ORFEUS: forma e música - Conde, Antónia Fialho (2016)
Abstract This communication reflects the work done in the Department of Civil Engineering and Architecture at the University of Beira Interior (Portugal), and still ongoing, in the framework of the project ORFEUS - The Tridentine Reform and music in the cloistral silence: the Monastery of S. Bento de Cástris (Project FCT EXPL/EPH-PAT/2253/2013) and aims to bring the debate to a contribution to the study of the specificity of the monastery of St. Bento de Cástris in the context of Cistercian architecture, in which the shape and the music are intertwined. In this way, two dissertations have been developed in Architecture (integrated master course of architecture of the University of Beira Interior) within the project ORFEUS, which are divided by the importance and contributions of the Cistercian Architecture in contemporary religious architecture, the morphology of the Cistercian churches and the relationship between architecture and music in the specific case study of the church of the monastery of St. Bento de Cástris. Resumo Esta comunicação reflecte o trabalho desenvolvido no Departamento de Engenharia Civil e Arquitectura da Universidade da Beira Interior, e ainda em curso, no âmbito do Projecto ORFEUS - A Reforma tridentina e a música no silêncio claustral: o mosteiro de S. Bento de Cástris (Projecto FCT EXPL/EPH- PAT/2253/2013) e pretende-se com esta comunicação trazer a debate um contributo para o estudo da especificidade do Mosteiro de S. Bento de Cástris, no contexto da arquitectura cisterciense, no qual a forma e a música se entrelaçam. Neste sentido foram desenvolvidas duas dissertações de mestrado integrado em Arquitectura, no âmbito do Projecto ORFEUS, que se repartem pela importância e contributos da Arquitectura Cisterciense na Arquitectura religiosa contemporânea, a morfologia das igrejas cistercienses e a relação entre a arquitectura e música patente no estudo de caso da igreja do Mosteiro de S. Bento de Cástris.